High-performance carbon battery and production process thereof

By adding water-soluble ammonium polymer and other additives to the electrolyte of carbon batteries, the problems of high internal resistance and increased gas production of carbon batteries are solved, and the battery performance is achieved with high discharge voltage, low resistance and good stability.

CN119650736AInactive Publication Date: 2025-03-18HANGZHOU CHANGMING BATTERY CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510181472.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-19
Publication Date
2025-03-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The electrolyte of carbon batteries has a high internal resistance and a small output current, which limits its application in high-power-demand equipment. Improved ion transfer efficiency may lead to increased gas production of the battery and poor structural stability.

Method used

The polymer is prepared by a specific synthetic method using a water-soluble ammonium salt polymer as an additive to the electrolyte solution, and additives such as ammonium acetate, polyacrylate, and polyacrylamide are added to the carbon battery to optimize the composition of the electrolyte.

Benefits of technology

It increases the discharge voltage of carbon batteries, reduces the gas discharge volume, enhances the stability of the battery, reduces the resistance, and is suitable for high-power demand equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention provides a high-performance carbon battery and a production process thereof. An electrolyte of the carbon battery comprises an aqueous solution of NH4Cl and ZnCl2 and an additive, and the additive is a water-soluble ammonium salt polymer. The battery provided by the invention has relatively high discharge voltage, less gassing and good stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a battery element, in particular to a high-performance carbon battery and a production process thereof. Background Art

[0002] Carbon battery is the full name of neutral zinc-manganese dioxide dry battery (zinc-manganese dry battery). It is a primary battery among chemical power sources and a disposable battery. The working principle of carbon battery is to convert the chemical energy of manganese dioxide and zinc into electrical energy through chemical reaction. During the discharge process, the zinc at the negative electrode undergoes oxidation reaction, and the manganese dioxide at the positive electrode combines with electrons. Carbon battery is mainly used for low power consumption. Due to its low price and safe and reliable use, it is widely used in daily household items, such as flashlights, remote controls, etc.

[0003] Carbon batteries have been developed since the mid-19th century and have always played an important role in the field of energy storage. With the development of science and technology, carbon batteries are currently mainly used in some low-power, low-current devices. The production cost of carbon batteries is low, and the production technology is relatively mature, which is suitable for cost-sensitive application scenarios. In addition, carbon batteries rely on the electrochemical properties of materials to discharge, have good structural stability, and have relatively mature model development. They have low current and can maintain power for a long time, and have good safety, so they have special industrial value.

[0004] In order to expand the applicable scenarios of carbon batteries, it is often necessary to increase the voltage and current of carbon batteries. The methods that can be used include using composite positive electrode materials, changing the battery structure and adjusting the composition of the electrolyte. In carbon batteries, the electrolyte transfers ions, allowing the battery to generate current. However, carbon battery electrolytes are often non-flowing, with relatively high internal resistance and low output current, which limits their application in high-power demand equipment. Adjusting the electrolyte composition to improve ion transfer efficiency has become an important strategy to improve battery voltage and current. However, improving ion transfer efficiency may often lead to increased battery gas production and poor structural stability. Therefore, it is particularly necessary to develop a carbon battery with high voltage, low resistance and low gas production. Summary of the invention

[0005] The present invention provides a water-soluble ammonium salt polymer, which is prepared by the following method: (1) adding methoxy polyethylene glycol-400 methacrylate to alkylamine and chloroform at 15-25°C for reaction.

[0006] (2) Cool down to 5-10°C, add chloromethyl ethylene oxide, and then increase the temperature to 25-45°C and 80-85°C to react.

[0007] (3) Cooling to 5-10°C, adding epichlorohydrin for reaction, and removing chloroform and unreacted monomers after the reaction is completed to obtain a water-soluble ammonium salt polymer.

[0008] In the present invention, the alkylamine may be ethylenediamine.

[0009] In the present invention, the mass ratio of the alkylamine to the chloroform may be 1:(20-30), for example, 1:25.

[0010] In the present invention, the mass ratio of the methoxy polyethylene glycol-400 methacrylate to the chloroform may be 2:(2.5-3.5), for example, 2:3.

[0011] In the present invention, the mass ratio of the chloromethyl ethylene oxide to the alkylamine may be 10:(2-4), for example, 10:3.

[0012] In the present invention, the mass ratio of the epichlorohydrin to the alkylamine may be (8-12):1, for example, 10:1.

[0013] The present invention provides a carbon battery, the electrolyte of which comprises an aqueous solution of NH4Cl and ZnCl2 and an additive; the additive is ammonium acetate, polyacrylamide, polyacrylamide and the above-mentioned water-soluble ammonium salt polymer.

[0014] In the present invention, the additive amount may be 0.8-1.2%, for example 1%, wherein the percentage (%) is the mass ratio of the additive to the electrolyte.

[0015] In the present invention, the electrolyte is preferably prepared by the following method: stirring the aqueous solution containing ZnCl2, NH4Cl and additives to obtain the electrolyte.

[0016] In the present invention, the carbon battery is preferably prepared by the following method, which comprises the following steps: mixing nano α-MnO2, expanded graphite and polytetrafluoroethylene, adding the electrolyte, and obtaining a positive electrode material.

[0017] In the present invention, the carbon battery is preferably prepared by the following method, which further comprises the following step: the positive electrode material is mixed with the electrolyte to obtain a slurry.

[0018] In the present invention, the carbon battery is preferably prepared by the following method, which further comprises the following steps: taking a 2 mm thick No. 7 battery zinc cylinder, using glass fiber diaphragm paper mixed with two layers of acrylic cellulose film paper as a composite diaphragm paper, adding the diaphragm paper to the zinc cylinder, injecting slurry, inserting a carbon rod as a current collector, applying sealing glue, adding a combination cap, and sealing on a machine.

[0019] The present invention provides a carbon battery, which comprises a negative zinc cylinder, a composite positive electrode, a diaphragm paper and an electrolyte, wherein the electrolyte is as described in any scheme of the present invention.

[0020] In the present invention, the battery can be prepared by the following process: adding a pulp paper layer into the zinc cylinder shell, adding a backing paper, and adding a battery core. Preferably, the battery core is the slurry prepared by the above method.

[0021] In the present invention, the preparation process of the above-mentioned battery can further include the following steps: pressing with the upper bowl, inserting the carbon rod, putting on a paper ring, sealing, putting on a second paper ring, putting on a steel cap, storing on a plate, brushing the bottom to test the electricity, putting on the little red cap, putting on the iron cover, and locking.

[0022] In the present invention, the preparation process of the above-mentioned battery can further include the following steps: applying a trademark, applying an iron bottom and heat shrinking, and heat shrinking the pair to obtain the above-mentioned battery.

[0023] In the present invention, the pulp paper layer may be a separator paper, and a composite separator paper may be a glass fiber separator paper mixed with two layers of acrylic cellulose film paper.

[0024] In the present invention, the plastic cover in the battery is conventional in the art, for example, a plastic cover obtained by stirring and injection molding polypropylene and calcium pink masterbatch.

[0025] In the present invention, the combined cap in the battery is conventional in the art, such as a combined cap formed by polyethylene injection molding and steel strip stamping.

[0026] The reagents and raw materials used in the present invention are commercially available.

[0027] The advantages of the battery of the present invention are: the battery provided by the present invention has a large discharge voltage, less gassing, and good stability. DETAILED DESCRIPTION

[0028] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0029] Source information of raw materials in the following examples: ammonium acetate (CH3COONH4), CAS: 631-61-8.

[0030] Polyacrylamide (CAS 9003-03-6), 40% hydrate.

[0031] Polyacrylamide (PAM) powder, 5-12 million, passed through 100 mesh sieve.

[0032] Additive preparation: Preparation of quaternary ammonium salt polymer.

[0033] 1.2 g of ethylenediamine and 30 g of chloroform were added into the reactor, the temperature of the feed liquid was controlled at 15°C, 20 g of methoxy polyethylene glycol-400 methacrylate (MPE400A) was slowly added, and the reaction was continued with stirring for 1 h after the addition was completed; the reaction temperature was lowered to 10°C, 4 g of chloromethyl ethylene oxide was added dropwise, the temperature was raised to 25°C, and the reaction was stirred for 30 min after 3 hours, the temperature in the reactor was raised to 85°C and the reaction was carried out for 30 min, the temperature was lowered to 10°C, 12 g of epichlorohydrin was added, the reaction was stirred and kept warm for 8 hours, and the chloroform and excess epichlorohydrin were removed by rotary evaporation to obtain 24 g of quaternary ammonium salt polymer, which was easily soluble in water.

[0034] Example 1: The electrolyte is 99 g of a mixture of NH4Cl (25%), ZnCl2 (10%), H2O (balance) and a trace amount of starch (about 0.5%), to which 1 g of ammonium acetate (mass content is 1 wt%, CH3COONH4) is added and stirred evenly.

[0035] The preparation method of the test battery includes the following steps: add 34g of nano α-MnO2 (average particle size of 50nm), 12.5g of expanded graphite, and 1g of polytetrafluoroethylene into the stirrer, stir for 5 minutes, and then add 2.5g of the above electrolyte for 10 minutes of wet stirring. After stirring evenly, pass through a 100-mesh sieve, granulate after sieving, and re-sieve to obtain positive electrode particles. Add 40g of electrolyte and stir to obtain slurry, which is used after being placed for 30 hours. Take a 2mm thick No. 7 battery zinc cylinder, use glass fiber diaphragm paper mixed with two layers of acrylic cellulose film paper as a composite diaphragm paper, add the diaphragm paper to the zinc cylinder, inject the aged slurry, add about 3.2g of slurry, insert a carbon rod as a current collector, apply sealing glue, add a combination cap, and seal it on the machine.

[0036] Example 2: The electrolyte is 100 g of a mixture of NH4Cl (25%), ZnCl2 (10%), H2O (balance) and a trace amount of starch (about 0.5%), which is stirred evenly.

[0037] The preparation method of the test battery includes the following steps: add 34g of nano α-MnO2 (average particle size of 50nm), 12.5g of expanded graphite, and 1g of polytetrafluoroethylene into the stirrer, stir for 5 minutes, and then add 2.5g of the above electrolyte for 10 minutes of wet stirring. After stirring evenly, pass through a 100-mesh sieve, granulate after sieving, and re-sieve to obtain positive electrode particles. Add 40g of electrolyte and stir to obtain slurry, which is used after being placed for 30 hours. Take a 2mm thick No. 7 battery zinc cylinder, use glass fiber diaphragm paper mixed with two layers of acrylic cellulose film paper as a composite diaphragm paper, add the diaphragm paper to the zinc cylinder, inject the aged slurry, add about 3.2g of slurry, insert a carbon rod as a current collector, apply sealing glue, add a combination cap, and seal it on the machine.

[0038] Example 3: The electrolyte is 99 g of a mixture of NH4Cl (25%), ZnCl2 (10%), H2O (balance) and a trace amount of starch (about 0.5%), 1 g of polyacrylamide (40% hydrate content, mass content based on the mass of polyacrylamide is 1 wt%) is added and stirred evenly.

[0039] The preparation method of the test battery includes the following steps: add 34g of nano α-MnO2 (average particle size of 50nm), 12.5g of expanded graphite, and 1g of polytetrafluoroethylene into the stirrer, stir for 5 minutes, and then add 2.5g of the above electrolyte for 10 minutes of wet stirring. After stirring evenly, pass through a 100-mesh sieve, granulate after sieving, and re-sieve to obtain positive electrode particles. Add 40g of electrolyte and stir to obtain slurry, which is used after being placed for 30 hours. Take a 2mm thick No. 7 battery zinc cylinder, use glass fiber diaphragm paper mixed with two layers of acrylic cellulose film paper as a composite diaphragm paper, add the diaphragm paper to the zinc cylinder, inject the aged slurry, add about 3.2g of slurry, insert a carbon rod as a current collector, apply sealing glue, add a combination cap, and seal it on the machine.

[0040] Example 4: The electrolyte is 99 g of a mixture of NH4Cl (25%), ZnCl2 (10%), H2O (balance) and a trace amount of starch (about 0.5%), 1 g of polyacrylamide (PAM) powder (1 wt%) is added and stirred evenly.

[0041] The preparation method of the test battery includes the following steps: add 34g of nano α-MnO2 (average particle size of 50nm), 12.5g of expanded graphite, and 1g of polytetrafluoroethylene into the stirrer, stir for 5 minutes, and then add 2.5g of the above electrolyte for 10 minutes of wet stirring. After stirring evenly, pass through a 100-mesh sieve, granulate after sieving, and re-sieve to obtain positive electrode particles. Add 40g of electrolyte and stir to obtain slurry, which is used after being placed for 30 hours. Take a 2mm thick No. 7 battery zinc cylinder, use glass fiber diaphragm paper mixed with two layers of acrylic cellulose film paper as a composite diaphragm paper, add the diaphragm paper to the zinc cylinder, inject the aged slurry, add about 3.2g of slurry, insert a carbon rod as a current collector, apply sealing glue, add a combination cap, and seal it on the machine.

[0042] Example 5: The electrolyte is 99 g of a mixture of NH4Cl (25%), ZnCl2 (10%), H2O (balance) and a trace amount of starch (about 1%), 1 g of polyquaternary ammonium salt (1 wt%) is added and stirred evenly.

[0043] The preparation method of the test battery includes the following steps: add 34g of nano α-MnO2 (average particle size of 50nm), 12.5g of expanded graphite, and 1g of polytetrafluoroethylene into the stirrer, stir for 5 minutes, and then add 2.5g of the above electrolyte for 10 minutes of wet stirring. After stirring evenly, pass through a 100-mesh sieve, granulate after sieving, and re-sieve to obtain positive electrode particles. Add 40g of electrolyte and stir to obtain slurry, which is used after being placed for 30 hours. Take a 2mm thick No. 7 battery zinc cylinder, use glass fiber diaphragm paper mixed with two layers of acrylic cellulose film paper as a composite diaphragm paper, add the diaphragm paper to the zinc cylinder, inject the aged slurry, add about 3.2g of slurry, insert a carbon rod as a current collector, apply sealing glue, add a combination cap, and seal it on the machine.

[0044] The battery materials obtained in Examples 1-4 are shown in Table 1.

[0045]

[0046] Note: The amount of polyacrylamide added is based on the mass of polyacrylamide.

[0047] Effect Example 1 Discharge and stability test.

[0048] The open circuit voltage (V) and internal resistance (mΩ) of the dry cells of Examples 1-5 were measured using a BS-VR3 battery internal resistance tester. The open circuit voltage measurement results are shown in Table 2.

[0049]

[0050] According to Table 2 above, the addition of additives did not significantly affect the open circuit voltage of the battery, and the addition of polyquaternary ammonium salt did not significantly weaken the battery performance.

[0051] The inventors further analyzed and found that the addition of polyacrylamide helps to reduce resistance. For example, in Example 4, the internal resistance is slightly reduced and excellent voltage stability can be maintained. The addition of polyquaternary ammonium salt does not significantly weaken the battery performance. Weak acid and alkaline salts (ammonium acetate and polyacrylamide) are not conducive to internal resistance.

[0052] According to the R-03 battery standard test process, the stability performance of the above battery test was tested, and a continuous discharge test was performed at a discharge current of 60mA. The results are shown in Table 3.

[0053]

[0054] The dry cell battery uses a zinc cylinder shell. Because the electrolyte is an acidic electrolyte, there is a defect of gas production. Storage at room temperature causes the battery efficiency to decrease. As shown in Table 3 above, the battery of the present invention has a lower gas production and a lower volume expansion coefficient. The addition of the polymer further improves the stability of the dry cell battery.

[0055] Comparative Example 1: Preparation of Bisphenol A Polymer-1: 2 mol of bisphenol A monomer (CAS: 80-05-7), 3 mol of di(4-bromophenyl)amine and 12 mol of 4,4'-dichlorodiphenyl sulfone were added to a reaction bottle, and 1800 ml of DMSO was added as solvent. Nitrogen was introduced, and then 110 g of sodium hydroxide and 100 ml of toluene were added. Salting-out reaction was carried out at 85 degrees Celsius for 6 hours. The temperature was raised to 200 degrees Celsius, the water in the reaction system was evaporated, and the reaction was continued for 7 hours. 0.2 mol of p-hydroxyaniline was added to the reaction system for condensation reaction with the polymer to obtain an aminated end-capped polymer, which was cooled to room temperature, crushed by a pulverizer, and passed through a 300 mesh sieve to obtain Bisphenol A Polymer-1.

[0056] Battery preparation: The electrolyte is a mixture of 99 g of NH4Cl (25%), ZnCl2 (10%), H2O (balance) and a trace amount of starch (about 0.5%), add 1 g of bisphenol A polymer-1 (1 wt%) and stir evenly.

[0057] The preparation method of the test battery includes the following steps: add 34g of nano α-MnO2 (average particle size of 50nm), 12.5g of expanded graphite, and 1g of polytetrafluoroethylene into the stirrer, stir for 5 minutes, and then add 2.5g of the above electrolyte for 10 minutes of wet stirring. After stirring evenly, pass through a 100-mesh sieve, granulate after sieving, and re-sieve to obtain positive electrode particles. Add 40g of electrolyte and stir to obtain slurry, which is used after being placed for 30 hours. Take a 2mm thick No. 7 battery zinc cylinder, use glass fiber diaphragm paper mixed with two layers of acrylic cellulose film paper as a composite diaphragm paper, add the diaphragm paper to the zinc cylinder, inject the aged slurry, add about 3.2g of slurry, insert a carbon rod as a current collector, apply sealing glue, add a combination cap, and seal it on the machine.

[0058] Comparative Example 2: Preparation of Bisphenol A Polymer-2: 2 mol of hexafluorobisphenol A monomer (CAS: 1478-61-1), 3 mol of di(4-bromophenyl)amine and 12 mol of 4,4'-dichlorodiphenyl sulfone were added to a reaction bottle, and 1800 ml of DMSO was added as solvent. Nitrogen was introduced, and then 110 g of sodium hydroxide and 100 ml of toluene were added. Salting-out reaction was carried out at 85 degrees Celsius for 6 hours. The temperature was raised to 200 degrees Celsius, the water in the reaction system was evaporated, and the reaction was continued for 7 hours. 0.2 mol of p-hydroxyaniline was added to the reaction system for condensation reaction with the polymer to obtain an aminated end-capped polymer, which was cooled to room temperature, crushed by a pulverizer, and passed through a 300 mesh sieve to obtain Bisphenol A Polymer-2.

[0059] Battery preparation: The electrolyte is a mixture of 99 g of NH4Cl (25%), ZnCl2 (10%), H2O (balance) and a trace amount of starch (about 0.5%), add 1 g of bisphenol A polymer-2 (1 wt%) and stir evenly.

[0060] The preparation method of the test battery includes the following steps: add 34g of nano α-MnO2 (average particle size of 50nm), 12.5g of expanded graphite, and 1g of polytetrafluoroethylene into the stirrer, stir for 5 minutes, and then add 2.5g of the above electrolyte for 10 minutes of wet stirring. After stirring evenly, pass through a 100-mesh sieve, granulate after sieving, and re-sieve to obtain positive electrode particles. Add 40g of electrolyte and stir to obtain slurry, which is used after being placed for 30 hours. Take a 2mm thick No. 7 battery zinc cylinder, use glass fiber diaphragm paper mixed with two layers of acrylic cellulose film paper as a composite diaphragm paper, add the diaphragm paper to the zinc cylinder, inject the aged slurry, add about 3.2g of slurry, insert a carbon rod as a current collector, apply sealing glue, add a combination cap, and seal it on the machine.

[0061] Comparative Example 3: Preparation of Bisphenol A Polymer-3: 2 mol of 4,4'-isopropyldiphenol monomer (CAS: 1478-61-1), 3 mol of di(4-bromophenyl)amine and 12 mol of 4,4'-dichlorodiphenyl sulfone were added to the reaction bottle, and 1800 ml of DMSO was added as solvent. Nitrogen was introduced, and then 110 g of sodium hydroxide and 100 ml of toluene were added. The salting-out reaction was carried out at 85 degrees Celsius for 6 hours. The temperature was raised to 200 degrees Celsius, the water in the reaction system was evaporated, and the reaction was continued for 7 hours. 0.2 mol of p-hydroxyaniline was added to the reaction system for condensation reaction with the polymer to obtain an aminated end-capped polymer, which was cooled to room temperature, crushed by a pulverizer, and passed through a 300 mesh sieve to obtain Bisphenol A Polymer-3.

[0062] Battery preparation: The electrolyte is a mixture of 99 g of NH4Cl (25%), ZnCl2 (10%), H2O (balance) and a trace amount of starch (about 0.5%), add 1 g of bisphenol A polymer-3 (1 wt%) and stir evenly.

[0063] The preparation method of the test battery includes the following steps: add 34g of nano α-MnO2 (average particle size of 50nm), 12.5g of expanded graphite, and 1g of polytetrafluoroethylene into the stirrer, stir for 5 minutes, and then add 2.5g of the above electrolyte for 10 minutes of wet stirring. After stirring evenly, pass through a 100-mesh sieve, granulate after sieving, and re-sieve to obtain positive electrode particles. Add 40g of electrolyte and stir to obtain slurry, which is used after being placed for 30 hours. Take a 2mm thick No. 7 battery zinc cylinder, use glass fiber diaphragm paper mixed with two layers of acrylic cellulose film paper as a composite diaphragm paper, add the diaphragm paper to the zinc cylinder, inject the aged slurry, add about 3.2g of slurry, insert a carbon rod as a current collector, apply sealing glue, add a combination cap, and seal it on the machine.

[0064] Comparative Example 4: Preparation of Bisphenol A Polymer-4: 2 mol of bisphenol AF monomer (CAS: 1478-61-1), 3 mol of di(4-bromophenyl)amine and 12 mol of 4,4'-dichlorodiphenyl sulfone were added to a reaction bottle, and 1800 ml of DMSO was added as solvent. Nitrogen was introduced, and then 110 g of sodium hydroxide and 100 ml of toluene were added. Salting-out reaction was carried out at 85 degrees Celsius for 6 hours. The temperature was raised to 200 degrees Celsius, the water in the reaction system was evaporated, and the reaction was continued for 7 hours. 0.2 mol of p-hydroxyaniline was added to the reaction system for condensation reaction with the polymer to obtain an aminated end-capped polymer, which was cooled to room temperature, crushed by a pulverizer, and passed through a 300 mesh sieve to obtain bisphenol A polymer-4.

[0065] Battery preparation: The electrolyte is a mixture of 99 g of NH4Cl (25%), ZnCl2 (10%), H2O (balance) and a trace amount of starch (about 0.5%), add 1 g of bisphenol A polymer-4 (1 wt%) and stir evenly.

[0066] The preparation method of the test battery includes the following steps: add 34g of nano α-MnO2 (average particle size of 50nm), 12.5g of expanded graphite, and 1g of polytetrafluoroethylene into the stirrer, stir for 5 minutes, and then add 2.5g of the above electrolyte for 10 minutes of wet stirring. After stirring evenly, pass through a 100-mesh sieve, granulate after sieving, and re-sieve to obtain positive electrode particles. Add 40g of electrolyte and stir to obtain slurry, which is used after being placed for 30 hours. Take a 2mm thick No. 7 battery zinc cylinder, use glass fiber diaphragm paper mixed with two layers of acrylic cellulose film paper as a composite diaphragm paper, add the diaphragm paper to the zinc cylinder, inject the aged slurry, add about 3.2g of slurry, insert a carbon rod as a current collector, apply sealing glue, add a combination cap, and seal it on the machine.

[0067] In this application, in order to explore the mechanism of the influence of polymers on the stability of dry batteries, the inventors used a large number of commercially available polymer materials, such as plastics, to dope dry batteries, but failed to obtain battery materials with good stability. The doping of plastics instead affected the mechanical properties and resistance of the battery. It is speculated that the conductivity and adhesion of plastics are poor, which is insufficient to provide the mass transfer electrochemical environment required by dry batteries.

[0068] Based on the above research, the inventors further studied adhesive and conductive materials, and speculated that polymers with strong adhesiveness and conductivity may help the stability of dry batteries. The polymer monomers of the polymer materials used in Comparative Examples 1-4 are bisphenol A monomers, which have improved conductivity. The corresponding monomers are shown in Table 4 below.

[0069]

[0070] The attenuation of the dry cell obtained was tested with reference to the above embodiment, and the discharge time of the obtained battery was tested at room temperature for 260 days in parallel. The discharge time was detected, and the results are shown in Table 5.

[0071]

[0072] Bisphenol A polymers have been used to improve battery performance due to their high conductivity. However, according to the above test results, improving the conductivity and adhesion of the material cannot effectively improve the stability of dry batteries. During storage, dry batteries will have a large power loss. Taking experimental errors into account, polybisphenol compounds cannot effectively improve the stability of battery materials.

[0073] The inventor accidentally discovered that adding a small amount of water-soluble ammonium salt polymer to a dry cell battery may help stabilize the structure of the dry cell battery, improve battery stability, and will not affect the battery voltage and current.

Claims

1. A carbon battery, characterized in that: The electrolyte comprises an aqueous solution of NH4Cl and ZnCl2 and an additive; the additive is a water-soluble ammonium salt polymer; the water-soluble ammonium salt polymer is polyacrylamide; or the water-soluble ammonium salt polymer is prepared by the following steps: (1) adding methoxy polyethylene glycol-400 methacrylate to alkylamine and chloroform at 15-25°C for reaction; (2) cooling to 5-10°C, adding chloromethyl ethylene oxide, and successively increasing the temperature to 25-45°C and 80-85°C for reaction; (3) cooling to 5-10°C, adding epichlorohydrin for reaction, and removing chloroform and unreacted monomers after the reaction is completed to obtain a water-soluble ammonium salt polymer.

2. The carbon battery according to claim 1, characterized in that: The mass content of NH4Cl in the electrolyte is 25%; and / or, the mass content of ZnCl2 in the electrolyte is 10%; and / or, the electrolyte further contains 0.1-1% starch.

3. The carbon battery according to claim 1, characterized in that: The mass content of NH4Cl in the electrolyte is 20-30%; and / or the mass content of ZnCl2 in the electrolyte is 5%-15%.

4. The carbon battery according to claim 1, characterized in that: The carbon battery comprises a positive electrode material, wherein the positive electrode material comprises manganese dioxide and a carbon material; and / or the carbon battery comprises a separator paper.

5. The carbon battery according to claim 1, characterized in that: The additive addition amount is 1%, wherein the percentage is the mass ratio of the additive to the electrolyte.

6. The carbon battery according to claim 1, characterized in that: The alkylamine is ethylenediamine; and / or, the mass ratio of the alkylamine to the chloroform is 1:25; and / or, the mass ratio of the methoxy polyethylene glycol-400 methacrylate to the chloroform is 2:3; and / or, the mass ratio of the chloromethyl ethylene oxide to the alkylamine is 10:3; and / or, the mass ratio of the epichlorohydrin to the alkylamine is 10:

1.

7. The carbon battery according to claim 1, characterized in that: The alkylamine is ethylenediamine; and / or, the mass ratio of the alkylamine to the chloroform is 1:(20-30); and / or, the mass ratio of the methoxy polyethylene glycol-400 methacrylate to the chloroform is 2:(2.5-3.5); and / or, the mass ratio of the chloromethyl ethylene oxide to the alkylamine is 10:(2-4); and / or, the mass ratio of the epichlorohydrin to the alkylamine is (8-12):

1.

8. A carbon battery production process as claimed in any one of claims 1 to 5, characterized in that: The method comprises the following steps: adding diaphragm paper into a zinc cylinder shell, adding a positive electrode material, inserting a carbon rod, and encapsulating to obtain a carbon battery; wherein the positive electrode material is prepared by the following method: mixing nano α-MnO2, expanded graphite and polytetrafluoroethylene, adding the electrolyte of the carbon battery described in any one of claims 1 to 5, and obtaining a composite positive electrode material.

9. The carbon battery production process according to claim 8, characterized in that: The method comprises the following steps: adding a pulp paper layer into the zinc cylinder shell, wherein the pulp paper layer comprises diaphragm paper, adding bottom paper, adding the positive electrode material, re-pressing with a bowl, inserting a carbon rod, applying a paper ring, sealing, applying a second paper ring, applying a steel cap, storing on a plate, brushing the bottom for electricity testing, applying a small red cap, applying an iron cover, locking the mouth, heat shrinking the iron bottom, and heat shrinking the opposite installation.

10. The carbon battery production process according to claim 8, characterized in that: The separator paper is glass fiber separator paper mixed with two layers of acrylic cellulose film paper.

Citation Information

Patent Citations

  • Mercury-free alkaline dry battery

    CN101682042A

  • Multifunctional polyquaternium and preparation method thereof

    CN113429560A

  • Carbon zinc-manganese dry battery with high current utilization rate and manufacturing process thereof

    CN113809345A

  • Water-based zinc ion battery electrolyte containing polyacrylate additive and water-based zinc ion battery

    CN117219887A

  • High-magnification columnar zinc-manganese battery

    CN212810349U